Back‐Illuminated Si‐Based Photoanode with Nickel Cobalt Oxide Catalytic Protection Layer. Issue 10 (26th September 2016) - Bae, Dowon; Mei, Bastian; Frydendal, Rasmus; Pedersen, Thomas; Seger, Brian; Hansen, Ole; Vesborg, Peter C. K.; Chorkendorff, Ib
Abstract: The front cover artwork is provided by Ib Chorkendorff, Dowon Bae, and co‐workers at the Technical University of Denmark (Denmark). The image highlights a time‐dependent improvement in the water oxidation reaction of a back‐side illuminated c‐Si‐based photoanode protected by a co‐sputtered thin film of NiCoOX with iron incorporation. Read the full text of the Article at10.1002/celc.201500554 . Abstract : "A co‐sputtered NiCoOX film coupled to Si is used as a protective catalyst for photocatalytic water oxidation under back‐side illumination; it shows a cathodic shift of the onset voltage (>50 mV) that is likely caused by the incorporation of Fe from KOH electrolyte. Once the activity of the sample is stabilized, no further degradation is observed over the following 6 days, indicating that the demonstrated configuration can be considered as a promising strategy for a bottom cell of the tandem water‐splitting device…" Find out more about the story behind the front cover research at10.1002/celc.201500554 .